2013
DOI: 10.1016/j.bbamem.2012.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of DMPC and DMPC/gemini liposomes with the cell membrane investigated by electrorotation

Abstract: The electrorotation technique was utilized to investigate the interactions between a mouse fibroblast cell line and zwitterionic liposomes formed by a natural phospholipid or cationic liposomes formulated with the same phospholipid and a cationic gemini surfactant. The application of this technique allowed an accurate characterization of the passive dielectric behavior of the plasma membrane by the determination of its specific capacitance and conductance. Changes of these parameters, upon interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…A previous study has indicated that the HANPs, only within the cell nucleus, could induce cytotoxicity, while the HANPs that remained in the perinuclear region or cytoplasm only caused local modifications to the morphology and structure of the cell membrane and exerted negligible inhibitory effects. 35,36,37 However, our results suggested that HANPs might interact with organelles, such as chondriosome and lysosomes (Figure 3), thus interfering with HUVEC survival and function although they concentrated in the cytoplasm (Figures 2 and 7). The uptake of NPs originated from an event of NPs adhering to the cell membrane, and this process was followed by the actual internalization via energy-dependent uptake pathways.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study has indicated that the HANPs, only within the cell nucleus, could induce cytotoxicity, while the HANPs that remained in the perinuclear region or cytoplasm only caused local modifications to the morphology and structure of the cell membrane and exerted negligible inhibitory effects. 35,36,37 However, our results suggested that HANPs might interact with organelles, such as chondriosome and lysosomes (Figure 3), thus interfering with HUVEC survival and function although they concentrated in the cytoplasm (Figures 2 and 7). The uptake of NPs originated from an event of NPs adhering to the cell membrane, and this process was followed by the actual internalization via energy-dependent uptake pathways.…”
Section: Discussionmentioning
confidence: 56%
“…Previous in-vitro experiments have shown that not only curcumin, but liposomes containing predominantly DMPC caused echinocyte formation [26]. This effect may be due to an interaction and incorporation of liposomal bilayers into the red blood cell membrane as described by Cosimati et al [27]. One potential limitation for the interpretation of this data was that the number of subjects per dose was low and the plasma concentrations varied within the groups.…”
Section: Discussionmentioning
confidence: 83%
“…Gemini QAS have much lower CMC (critical micelle concentrations) in comparison to monomeric surfactants [3]. Gemini QAS surfactants are able to form bilayer aggregates, like liposomes, and are extensively studied as potential non-viral gene delivery systems or drug carriers [4][5][6]. The activity of gemini QAS against microorganisms is generally stronger in comparison to the corresponding monomeric compounds and depends on the structure of the gemini molecule [7].…”
Section: Introductionmentioning
confidence: 99%